Exploring the Concept of Integrity—Toward a CraftInspired Interpretation - Thomassen, Ole Jacob; Strand, Roger; Heggen, Kristin (Nordic Journal of Working Life Studies, 2017)
The concept of integrity is used as a psychosocial concept to describe tensions and dilemmas experienced by professional and semi-professional workers in a neoliberal working life. In Norway, the concept has even been included in the Working Environment Act. In general terms, the concept refers to the degree to which professionals experience that their internalized professional standards can be realized. While supporting the general relevance of integrity as an important concept for assessing an important psychosocial challenge in Nordic working life, we propose that integrity should not be addressed as a psychological phenomenon. We suggest that it in line with a more sociological orientation is addressed as a craft issue. This interpretation is inspired by Richard Sennett’s concept of craftwork. Understanding integrity as a craft phenomenon inspires workplace critique within neoliberal work organizations